2023
DOI: 10.1186/s12967-023-04276-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of impaired sensitivity to thyroid hormones with hyperuricemia through obesity in the euthyroid population

Abstract: Background Impaired sensitivity to thyroid hormones is a newly proposed clinical entity associated with hyperuricemia in the subclinical hypothyroid population. However, it is unknown whether the association exists in the euthyroid population. This study aimed to explore the association of impaired sensitivity to thyroid hormones (assessed by the thyroid feedback quantile-based index [TFQI], parametric thyroid feedback quantile-based index [PTFQI], thyrotrophic thyroxine resistance index [TT4RI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…People of diabetes or other metabolic disorders should be aware of the thyroid function resistance and its consequences, including lipid pattern ( 35 ), renal and liver functions ( 13 , 36 ), atherosclerosis ( 37 ), cognition performance ( 38 ) and mortality ( 12 ). Meanwhile, previous studies have demonstrated a close association between thyroid hormones sensitivity and metabolic disorders based on cross-sectional designs ( 39 ). The causal and temporal relationship needs more data to interpret the clinical relevance of thyroid hormones sensitivity in depth.…”
Section: Discussionmentioning
confidence: 99%
“…People of diabetes or other metabolic disorders should be aware of the thyroid function resistance and its consequences, including lipid pattern ( 35 ), renal and liver functions ( 13 , 36 ), atherosclerosis ( 37 ), cognition performance ( 38 ) and mortality ( 12 ). Meanwhile, previous studies have demonstrated a close association between thyroid hormones sensitivity and metabolic disorders based on cross-sectional designs ( 39 ). The causal and temporal relationship needs more data to interpret the clinical relevance of thyroid hormones sensitivity in depth.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a mediation analysis to assess the direct and indirect associations between the TyG index and CVD events via higher hsCRP. In brief, a higher TyG index (≥ median value of 8.6) was used as a predictor variable (X), a higher hsCRP level (≥ 1.0 mg/L) was used as a mediator (M) and a CVD event was used as the outcome variable (Y), as widely used in previous studies to quantify the mediating effect [ 36 ]. Meanwhile, the mediating effect of hsCPR on CVD events through the TyG index was similarly evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…Given the difficulty in directly measuring thyroid hormone sensitivity in clinical practice, we employed the TFQI, TSHI, TT4RI, and fT4/fT3 ratio as surrogate markers. These indices have been validated across numerous studies, underscoring their clinical value and accuracy in evaluating the sensitivity to thyroid hormone [ 20 22 ]. Indices of central thyroid hormone sensitivity included the TFQI (TFQI = cdf fT4 − (1 − cdf TSH), where cdf is the cumulative distribution function), TSHI (TSHI = ln TSH (mIU/L) + 0.1345 × fT4 (pmol/L)), and TT4RI (TT4RI = fT4 (pmol/L) × TSH (mIU/L)), and peripheral thyroid sensitivity was calculated as fT4/fT3 [ 19 ].…”
Section: Methodsmentioning
confidence: 99%